Learning Approaches as a Means to Understand Difficulties and Opportunities in Type 2 Diabetes Self-Management Training: A Qualitative Content Analysis of Two German Educational Curricula. Issue 6 (2nd November 2022) - Healy, Karl V.; Weise, Solveig; Fink, Astrid; Frese, Thomas; Richter, Matthias; Knöchelmann, Anja
ABSTRACT: Background: Diabetes self-management education (DSME) improves disease-specific markers (HbA1c levels and bodyweight) and prevents disease-related complications. Yet, patients do not seem to benefit equally from such education, likely because of differences in approaches to learning. Purpose: We investigated which learning approaches are best addressed by diabetes curricula and suggest improvements in curriculum design. Methods: Two of the most popular German type 2 DSME curricula were studied. We used qualitative content analysis to build a systematic coding frame, extracting and connecting categories of meaning from the material. Criteria for categories were drawn from research on learning preferences in adult Germans. Results: Both curricula mainly address participants preferring educator-guided and application-driven learning. One of the curricula more actively involves its participants with open discussions and personal goal-setting and shows a stronger emphasis on social support strategies. Discussion: Different learning approaches are not met equally in the curricula, which might create unique difficulties for participants of DSME. Translation to Health Education Practice: Introducing personal goal-setting and progress monitoring in DSME should benefit participants with passive approaches to learning. Offering additional course material could diversify teaching methods and satisfy theoretically driven people. All DSME programs should emphasize social support strategies. A AJHE Self-Study quiz is online for this article via the SHAPE America Online Institute (SAOI) http://portal.shapeamerica.org/trn-Webinars